2009
DOI: 10.1152/jn.91092.2008
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Globus Pallidus Internus in the Parkinsonian Primate: Local Entrainment and Suppression of Low-Frequency Oscillations

Abstract: McCairn KW, Turner RS. Deep brain stimulation of the globus pallidus internus in the parkinsonian primate: local entrainment and suppression of low-frequency oscillations. J Neurophysiol 101: 1941-1960, 2009. First published January 21, 2009 doi:10.1152/jn.91092.2008. Competing theories seek to account for the therapeutic effects of high-frequency deep brain stimulation (DBS) of the internal globus pallidus (GPi) for medically intractable Parkinson's disease. To investigate this question, we studied the spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
115
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 86 publications
11
115
2
Order By: Relevance
“…Recordings from PD patients, MPTPtreated NHPs, and 6-OHDA-treated rats have recently shown that (i) the regularity of the stimulation (i.e., using constant interpulse intervals) and the high frequency are both relevant to achieve motor restoration (5,36,48,81); (ii) STN and GPi neurons have exaggerated bursting and oscillatory firing patterns under PD conditions, which may correlate with the movement disorders (6, 52); (iii) HFS results into a more regular (i.e., tonic) firing of the neurons in both the stimulated site and the structures downstream from it (15,17,22,23,25,26); and (iv) the measures of firing regularity (e.g., entropy, coefficient of variation, etc.) correlate with the reduction of movement disorders (22,32,33,36,49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recordings from PD patients, MPTPtreated NHPs, and 6-OHDA-treated rats have recently shown that (i) the regularity of the stimulation (i.e., using constant interpulse intervals) and the high frequency are both relevant to achieve motor restoration (5,36,48,81); (ii) STN and GPi neurons have exaggerated bursting and oscillatory firing patterns under PD conditions, which may correlate with the movement disorders (6, 52); (iii) HFS results into a more regular (i.e., tonic) firing of the neurons in both the stimulated site and the structures downstream from it (15,17,22,23,25,26); and (iv) the measures of firing regularity (e.g., entropy, coefficient of variation, etc.) correlate with the reduction of movement disorders (22,32,33,36,49).…”
Section: Discussionmentioning
confidence: 99%
“…Reinforcement is maximal for the clinically relevant 130-Hz stimulation and restores a more normal activity in the nuclei downstream. These results suggest that reinforcement may be pivotal to achieve pattern regularization and restore the neural activity in the nuclei downstream and may stem from frequency-selective resonant properties of the loop.igh-frequency (i.e., above 100 Hz) deep brain stimulation (HFS) of the basal ganglia (BG) and thalamus is clinically recognized to treat movement disorders in Parkinson's disease (PD) (1-4), but its therapeutic mechanisms remain unclear (5, 6).Early hypotheses about HFS were derived from the rate-based model of the BG function (7,8) and postulated the disruption of the output of the BG-thalamic system via either the inactivation of neurons in the stimulated site (target) (9-15), which would provide an effect similar to a surgical lesion, or the abnormal excitation of axons projecting out of the target (16-19), which would disrupt the neuronal activity in the structures downstream, including any pathophysiological activity (20).More recently, an ever-growing number of experiments in PD humans and animal models of Parkinsonism has indicated that HFS affects the firing patterns of the neurons rather than the mean firing rate both in the target and the structures downstream (18,19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and it replaces repetitive low-frequency (i.e., ≤50 Hz) bursting patterns with regularized (i.e., more tonic) patterns at higher frequencies (25,26). It has been proposed that increased pattern regularity of neurons in the target may be therapeutic (5, 32-37), but it is still unknown how this regularity comes about with HFS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, STN DBS in patients with PD suppresses beta-band oscillations in the basal ganglia and reduces the aforementioned pathological coupling between beta-band phase and gamma-band amplitudes in MC [307][308][309][310]. GPi DBS also reduces beta-band oscillations in GPi and MC [297,311]. These findings suggest that DBS may exert some of its effects by disrupting abnormal cortical synchronization.…”
Section: Dbs Mechanism Of Actionmentioning
confidence: 94%
“…Later studies focused on changes in the temporal pattern of neuronal firing during stimulation. HFS resulted in finely timed changes in firing with latencies as short as a few milliseconds in the primate GP during STN (Hashimoto et al, 2003;Kita et al, 2005) and GP (Bar-Gad et al, 2004;McCairn and Turner, 2009) stimulation, and in the thalamus during STN and GPi (Montgomery, 2006) stimulation. Furthermore, HFS was shown to affect other firing pattern properties including oscillatory and bursty activity (Meissner et al, 2005;Montgomery, 2006;Dorval et al, 2008;Hahn et al, 2008;Xu et al, 2008;McCairn and Turner, 2009).…”
Section: Introductionmentioning
confidence: 99%